2020
DOI: 10.1097/cmr.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of combined targeted therapy and concurrent radiotherapy in metastatic melanoma patients: a single-center retrospective analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For this combination, mainly an increased risk of skin toxicity has been described in the literature [ 21 ]. Although the study of Hecht et al observed an increased risk in grade ≥2 toxicity and worse OS when BRAFi was continued during SRT due to its radiosensitizing properties, the study of Ziegler et al did not see these side-effects when BRAFi was combined with MEKi [ 30 , 31 ], with the hypothesis that MEKi can mitigate the occurrence of skin side effects [ 32 ]. In this study, we did not observe skin toxicity since the dose to the skin is usually limited with SRT.…”
Section: Discussionmentioning
confidence: 99%
“…For this combination, mainly an increased risk of skin toxicity has been described in the literature [ 21 ]. Although the study of Hecht et al observed an increased risk in grade ≥2 toxicity and worse OS when BRAFi was continued during SRT due to its radiosensitizing properties, the study of Ziegler et al did not see these side-effects when BRAFi was combined with MEKi [ 30 , 31 ], with the hypothesis that MEKi can mitigate the occurrence of skin side effects [ 32 ]. In this study, we did not observe skin toxicity since the dose to the skin is usually limited with SRT.…”
Section: Discussionmentioning
confidence: 99%